Ocular and Nonocular Adverse Events during 3 Years of Soft Contact Lens Wear in Children. Issue 6 (12th June 2022) - Gaume Giannoni, Amber; Robich, Matt; Berntsen, David A.; Jones-Jordan, Lisa A.; Mutti, Donald O.; Myers, Jill; Shaw, Kimberly; Walker, Maria K.; Walline, Jeffrey J.; ,
Abstract : SIGNIFICANCE: Children are being fitted at younger ages with soft contact lenses for myopia control. This 3-year investigation of adverse events related to contact lens wear in 7- to 11-year-old participants helps optometrists understand what to expect when fitting children with soft contact lenses. PURPOSE: The purpose of this article is to report the frequency and type of ocular and nonocular adverse events related to soft contact lens wear in children. METHODS: Seven- to 11-year-old children wore soft contact lenses for 3 years. Adverse events were defined by a slit-lamp examination finding of grade 3 or worse; parental report of a clinically meaningful change (determined by the examiner) in eyes, vision, or health; or a clinically meaningful response (determined by examiner) to a symptom checklist. Adverse events were categorized and reported by examiners and finalized by the Executive Committee. The presence or absence of an infiltrate and a list of diagnoses was determined at the conclusion of the study. RESULTS: The 294 participants wore their contact lenses 73.0 ± 26.5 hours per week, and 220 (74.8%) encountered at least 1 adverse event. Of the 432 adverse events, 75.2% were ocular, and 24.8% were nonocular. Contact lens wear was probably or definitely related to 60.6% of the ocular and 2.8% of the nonocular adverse events. None of the ocular adverse events were serious or severe or caused permanent contact lens discontinuation. The corneal infiltrate incidence was 185 cases per 10, 000 patient-years of wear (95% confidence interval, 110 to 294). The incidence of moderate ocular adverse events that were definitely or probably related to contact lens wear was 405 cases per 10, 000 patient-years of wear (95% confidence interval, 286 to 557). CONCLUSIONS: The adverse events experienced by 7- to 11–year-old myopic children rarely required meaningful treatment and never led to permanent discontinuation of contact lens wear or loss of best-corrected vision.